2016
DOI: 10.1007/978-3-319-46279-0_7
|View full text |Cite
|
Sign up to set email alerts
|

A Forensic Methodology for Analyzing Nintendo 3DS Devices

Abstract: Handheld video game consoles have evolved much like their desktop counterparts over the years. The most recent eighth generation of game consoles are now defined not by their ability to interact online using a web browser, but by the social media facilities they now provide. This chapter describes a forensic methodology for analyzing Nintendo 3DS handheld video game consoles, demonstrating their potential for misuse and highlighting areas where evidence may reside. Empirical research has led to the formulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…1. Practitioner knowledge: The phrase 'Nintendo forensics' is acknowledged by a number of practitioners (Carvey, 2009;Jones, 2016;Read et al, 2016) referring to the use of push-button parsing tools which require little to no understanding of their underlying workings. Whilst this is not applicable in all cases, arguably such mentalities do still exist, where it is easy to initiate a process and draw conclusions solely on its completion and results.…”
Section: The 'Grey Area': Te Ue or Tl?mentioning
confidence: 99%
“…1. Practitioner knowledge: The phrase 'Nintendo forensics' is acknowledged by a number of practitioners (Carvey, 2009;Jones, 2016;Read et al, 2016) referring to the use of push-button parsing tools which require little to no understanding of their underlying workings. Whilst this is not applicable in all cases, arguably such mentalities do still exist, where it is easy to initiate a process and draw conclusions solely on its completion and results.…”
Section: The 'Grey Area': Te Ue or Tl?mentioning
confidence: 99%
“…There has been considerable work to date (Conrad 2010, Davies 2015, Moore 2014, Read 2016, Pessolano 2019, Barr-Smith 2021 highlighting the possible evidence sources that can be found in computer games consoles and best practices for extracting, analysing and presenting this information in a forensically sound manner. This previous research has shown that for a number of these systems the functionality of these game consoles makes them a potentially useful source of evidence, one that may be overlooked.…”
Section: Introductionmentioning
confidence: 99%